2021
DOI: 10.1017/s0950268821002314
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among university students in Lebanon

Abstract: Little is known about the decision-making process of college students in Lebanon regarding coronavirus disease-2019 (COVID-19) vaccination. The aim of this study was to identify factors predicting behavioural intentions of students enrolled at the American University of Beirut to obtain a COVID-19 vaccine. A total of 3805 students were randomly selected. Participants were divided into three groups: vaccine accepting (willing to take or already took the vaccine), vaccine hesitant (hesitant to take the vaccine) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 41 publications
2
32
3
Order By: Relevance
“…Another study conducted among Italian university students also found gender, major, and lower academic level as significant predictors of vaccine hesitancy [ 50 ]. University rank was also found as significant predictor of vaccine hesitancy among university students of Lebanon [ 17 ]. Our study found that the public university students reported negative knowledge and attitude compared to private university students.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted among Italian university students also found gender, major, and lower academic level as significant predictors of vaccine hesitancy [ 50 ]. University rank was also found as significant predictor of vaccine hesitancy among university students of Lebanon [ 17 ]. Our study found that the public university students reported negative knowledge and attitude compared to private university students.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Arab Emirates and Jordan, the main motivators for vaccine acceptability included the safety and efficacy of the vaccine, followed by a low risk of side effects, and higher overall protection ( 23 , 24 ). A study among university students in Lebanon revealed that a lower level of knowledge about the COVID-19 disease was associated with higher vaccine hesitancy ( 25 ). With numerous conspiracies about the vaccine on social media platforms, it is critical to investigate attitudes toward the vaccine and the reasons behind the willingness to get vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…Table S1: Strobe Statement for the study, Table S2: Studies conducted on the general population of other LMICs testing vaccine acceptance and related factors. References [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%